Toolkit to build resilience and sustainability without growth - Paulson, Susan Ann (Sustainability in Debate, 2016)
Review of: D’Alisa, Giacomo, Federico Demaria, and Giorgos Kallis. Degrowth: A vocabulary for a new era. Routledge, 2014. 220 pages. ISBN: 978-1-138-00076-6